Analisa Kesalahan Pemodelan Data Pasang Surut Stasiun Tanjung Priok - Prasetyo, Agus Ari; Zakaria, Ahmad; Welly, Margareta (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2016)
This research was conducted to study the characteristics of tides and tidal make synthetic model.The data used tide data hourly to the length of the data in 1985-1987 at the station Tanjung Priok,Jakarta province, Indonesia.The modeling is performed using a data length of 15 daily or for any length of data to 360 hoursand data 30 daily or for any length of data 720. Using data from tide observations obtained andapply Anfor equations and method least squares can be generated model of periodic tidal hourly.Model periodic tidal of tidal observation data is assumed as the model data obtained by using 9tidal harmonic components. From the modeling results and the measured data can be seen thecorrelation coefficient and the value of modeling errors.Based on these results we can conclude tidal hourly synthetic time series obtained significantlyapproaching tidal measurable. The correlation coefficient was very good, the value of the averagecorrelation coefficient models 30 daily periodic observation is 0.9377 and the average ofcorrelation coefficient models 15 daily periodic observation is 0.9571. From this research can beseen the value of a good tide data and allow for cost saving tide observations with 15 days ofobservation.keywords: daily tidal, the value of modeling errors, correlation coefficient